Pengaruh PER dan PBV terhadap Harga Saham Perusahaan Sektor Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2021 - 2022 - Reni Rismawati,; Siti Nurcahyati, (Journal of Management and Creative Business, 2026)
This study aims to determine the effect of Price Earning Ratio (PER) and Price to Book Value (PBV) on stock prices in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2022 period. This research uses a quantitative method with secondary data obtained from the companies’ annual financial statements. The population of this study consists of banking sector companies listed on the IDX, while the research sample was determined using a purposive sampling technique based on specific criteria relevant to the study objectives. The data were analyzed using SPSS version 25 through statistical testing to examine both partial and simultaneous effects. The results show that Price Earning Ratio (PER) has no significant effect on stock prices, while Price to Book Value (PBV) has an effect on stock prices. Simultaneously, PER and PBV influence stock prices, indicating that market valuation indicators can provide information for investors in assessing stock performance and making investment decisions in the banking sector.